2017
DOI: 10.3389/fphys.2017.00944
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylamine N-oxide Supplementation Abolishes the Cardioprotective Effects of Voluntary Exercise in Mice Fed a Western Diet

Abstract: Excessive consumption of western diet (WD) induces obesity, resulting in cardiac dysfunction. Voluntary exercise ameliorates WD-induced obesity, but its effect on cardiac dysfunction remains unclear. Recent evidence suggests that elevated trimethylamine N-oxide (TMAO), a gut microbe-derived metabolite, can impair cardiac function in WD-induced obesity. We hypothesized that cardiac dysfunction in WD-induced obesity would be prevented by voluntary exercise but abolished by TMAO supplementation. Male CD1 mice fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 40 publications
(67 reference statements)
0
28
0
1
Order By: Relevance
“…18,65 Additionally, Ma et al 66 demonstrated that TMAO upregulated vascular cell adhesion molecule (VCAM)-1 expression by activating protein kinase C (PKC)/NF-kB, which directly resulted in endothelial dysfunction that was characterized by reduced selfÀhealing capacity and increased monocyte adhesion. In a study to investigate whether inhibiting TMAO prevented myocardial inflammation, Zhang et al 67 discovered that TMAO might induce myocardial inflammation by elevating TNF-a levels and TMAO biogenesis and metabolism. Dietary nutrients (ie, choline) are biotransformed into TMA by TMA lyases (ie, cutC/D) in the gut.…”
Section: Pathological Mechanisms Of Tmao In Hfmentioning
confidence: 99%
“…18,65 Additionally, Ma et al 66 demonstrated that TMAO upregulated vascular cell adhesion molecule (VCAM)-1 expression by activating protein kinase C (PKC)/NF-kB, which directly resulted in endothelial dysfunction that was characterized by reduced selfÀhealing capacity and increased monocyte adhesion. In a study to investigate whether inhibiting TMAO prevented myocardial inflammation, Zhang et al 67 discovered that TMAO might induce myocardial inflammation by elevating TNF-a levels and TMAO biogenesis and metabolism. Dietary nutrients (ie, choline) are biotransformed into TMA by TMA lyases (ie, cutC/D) in the gut.…”
Section: Pathological Mechanisms Of Tmao In Hfmentioning
confidence: 99%
“…An animal study showed that voluntary exercise normalizes the plasma TMAO levels and prevents cardiac dysfunction in western diet-induced obese mice. This effect was reversed by concomitant administration of TMAO and abrogated the beneficial effects [49].…”
Section: Therapeutic Strategymentioning
confidence: 99%
“…Some clinical studies have reported TMAO levels to be higher with advanced left ventricular diastolic dysfunction in heart failure than in non-heart failure (Cannon and McMurray, 2014; Tang et al, 2014; Tang et al, 2015b). Several animal studies have suggested that elevated TMAO levels have a strong association with cardiac fibrosis and contribute to heart failure (Chen K. et al, 2017; Zhang et al, 2017; Li et al, 2018). However, the roles and mechanisms of TMAO-mediated cardiac fibrosis are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%